1961
DOI: 10.1063/1.1728376
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication of Polymers

Abstract: Previous work on the lubrication of polymers is reviewed and the explanations which have been advanced are examined and are shown to be inadequate. An alternative mechanism of polymer lubrication is proposed which is based on the hypothesis that when a lubricant is applied to a polymer it is possible for the lubricant molecules to penetrate the polymer and alter its mechanical properties. An investigation into the lubrication behavior of textile polymers is described and an explanation of the results of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…He suggested that the increase in the contact area is the more significant effect so that the aqueous lubrication character is rather poor [10,11]. This latter effect has been confirmed within the considered contact as detailed in Ref.…”
Section: Abrasive Wear Tests and Experimental Proceduresmentioning
confidence: 60%
“…He suggested that the increase in the contact area is the more significant effect so that the aqueous lubrication character is rather poor [10,11]. This latter effect has been confirmed within the considered contact as detailed in Ref.…”
Section: Abrasive Wear Tests and Experimental Proceduresmentioning
confidence: 60%
“…Such an initiation and development of fatigue cracks under a load would then lead to fatigue wear of the PTFE composites. This, in turn, reduces the mechanical strength and load‐supporting capacity of PTFE composites and, hence, deteriorates the tribological behavior of the PTFE composites under higher loads 10–12. Accordingly, it was supposed that the good solid compatibility between PTFE and metal powders (such as Cu, Pb, and Ni) as fillers accounts for the excellent tribological behavior of Cu‐, Pb‐, and Ni‐filled PTFE composites.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work indicated that PTFE and its composites filled with various inorganic fillers registered a considerably high friction coefficient and/or wear at a certain high load 8, 9. It was suggested that under lubrication with liquid paraffin the absorption and osmosis of liquid paraffin into the microdefects in the PTFE composites reduces the mechanical strength and load‐supporting capacity of PTFE composites 10–12. This would lead to the deterioration of the tribological behavior of PTFE composites under higher loads as lubricated by liquid paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, 10 pulses are able to produce a ®lm about 10 nm thick. 3 The ®lms prepared by either procedure were washed carefully with water and methanol and dried in a stream of air at room temperature. The ®lm thickness was estimated by a TALYSURF 5 stylus instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Since boundary lubrication occurs as a consequence of molecular adsorption, lubrication becomes more eective with longer-chain molecules until an optimum is achieved. 3 The highviscosity lubricants derived from a homologous series of compounds tend to increase the drag force; in addition, adsorption and absorption of lubricants may also cause chemical changes and plasticisation of the polymer surface. This has two implications: the shear strength reduces to give a low friction coecient or there may be observed an increased wear due to ®lm transfer 4 and additional drag forces due to the lubricant.…”
Section: Introductionmentioning
confidence: 99%